Analisis Kemampuan Pemecahan Masalah Matematis Peserta Didik pada Materi Peluang - Shafa Khadijah Rahmat; Hilman Robbany Arham (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Students' problem solving skills are very important for everyone who will apply them both in other fields of study and in everyday life. The purpose of this study is to analyze the mathematical problem solving abilities of class VIII students in the 2021/2022 academic year. The sample in this study was class VIII students totaling 16 students who were taken randomly at one school in Karawang. This research is a descriptive research, while the data collection technique is done by giving 3 questions about the mathematical problem solving ability test. After the mathematical problem solving ability test is done, students will be divided into 3 categories, namely high, medium, and low. The results of the analysis in this study state that indicator 1 is in the medium category with a percentage of 68.75%, then the second indicator is in the medium category with a percentage of 50%, and the third and fourth indicators are in the low category with a percentage of 31.25% and 18.75 respectively. %. The average mathematical problem solving ability of students is 42.18% and is included in the medium category. The conclusions obtained in this study are that the average ability of students on the material opportunity is in the moderate category, especially in its application, other difficulties faced by students are found when students have not been able to understand the problems in questions or in the concept of arithmetic operations.Kemampuan pemecahan masalah peserta didik sangatlah penting untuk semua orang yang akan menerapkannya, baik dalam bidang studi lain di luar matematika maupun dalam kehidupan sehari-hari. Tujuan dari penelitian ini yaitu untuk menganalisis kemampuan pemecahan masalah matematis peserta didik kelas VIII tahun ajaran 2021/2022. Sampel pada penelitian ini adalah peserta didik kelas VIII berjumlah 16 peserta didik yang diambil secara acak pada salah satu sekolah di Karawang. Penelitian ini merupakan penelitian deskriptif sedangkan Teknik pengumpulan data dilakukan dengan pemberian soal tes kemampuan pemecahan masalah matematis sebanyak 3 (tiga) soal. Setelah dilakukan tes kemampuan pemecahan masalah matematis, peserta didik akan dibagi menjadi 3 (tiga) kategori yaitu tinggi, sedang, dan rendah. Hasil analisis pada penelitian ini menyatakan bahwa pada indikator pertama berkategori sedang dengan presentase 68,75%, lalu indikator kedua berkategori sedang dengan presentase 50%, dan indikator ketiga dan keempat berkategori rendah dengan masing-masing presentase yaitu 31,25% dan 18,75%. Adapun rata-rata kemampuan pemecahan masalah matematis peserta didik sebesar 42,18% dan termasuk dalam kategori sedang. Simpulan yang didapat pada penelitian ini adalah rata-rata kemampuan peserta didik pada materi peluang masuk pada kategori sedang terutama dalam penerapannya, kesulitan lain yang dihadapi peserta didik ditemukan Ketika peserta didik belum mampu memahami permasalahan pada soal ataupun pada konsep operasi hitung.